PREVIOUS CROP AND NITROGEN FERTILIZATION IN CORN UNDER NO-TILLAGE SYSTEM - DENIS AUGUSTO DA SILVA (Revista Brasileira de Milho e Sorgo, 2006)
The use of previous crop that has capacity of supplying nitrogen to corn – by symbiotic fixation or nitrogen recycling – is of great importance to yield maintenance. The objective of this study was to evaluate the effect of previous crop associated to nitrogen rates in the agronomic performance of corn crop. This work was conducted in the Núcleo de Ciências Agrárias in the Federal University of Mato Grosso do Sul (UFMS) campus – located in Dourados, MS – during the 2001/02 agricultural year. The experiment was disposed in split-plot randomized complete block design with six replications. The main plot was three previous crops – black oat, hairy vetch and oilseed radish. The split plot had six nitrogen rates – zero, 50, 100, 150, 200 and 250 kg ha-1. Based on the results, corn grown after black oat responds positively to nitrogen fertilization, with maximum grain yield with N rates of 205 kg ha-1. After oilseed radish there is also a good response to nitrogen fertilization, however a lower rate could be used in order to get the maximum grain yield (175 kg ha-1). Corn grown after hairy vetch under no-tillage has no response to nitrogen fertilization, though yield is higher than black oat/corn and oilseed radish/corn crop sequences, when nitrogen fertilization is not used.